Fracture Toughness of Monolithic Zirconia and Lithium Disilicate CAD/CAM Endocrown - Suci, Aldrina Wulan Eka; Ratnasari, Dina; Dwisaptarini, Ade Prijanti; Elline, Elline (Journal of Indonesian Dental Association, 2023)
Introduction: Endocrown is an indirect restoration following the endodontic treatment made of ceramic material as a substitute for post core crown. The endocrown is cemented to the inner wall of the pulp chamber and to the cavity margins to increase the macromechanical retention. Material commonly used are monolithic zirconia and lithium disilicate; both can be obtained using the CAD/CAM technique. Good endocrown restoration must be able to handle the chewing workload especially on the posterior tooth. Objective: To determine the difference in fracture toughness of monolithic zirconia and lithium disilicate CAD/CAM endocrown. Methods: This study used 6 endocrown CAD/CAM samples, attached to typodont prototype in 3D resin printing model produced by the printing machine. Samples were divided into 2 groups. Group A were monolithic zirconia endocrowns and group B were lithium disilicate endocrowns. The fracture toughness was calculated using the Universal Testing Machine (UTM). Results: Fracture toughness of the monolithic zirconia endocrown were 2.747 N and lithium disilicate were 769 N. The unpaired t test showed that there was significant difference in fracture toughness between groups (p < 0,05). Conclusion: Monolithic zirconia endocrown has a higher fracture toughness compared to the lithium disilicate endocrown, but lithium disilicate is more recommended as an endocrown restoration material because its fracture toughness is closer to masticatory load of posterior teeth.